Is gender inequality in the domestic sphere associated with psychological distress among women and men? Results from the Northern Swedish Cohort. Issue 3 (12th October 2010) - Harryson, Lisa; Novo, Mehmed; Hammarström, Anne
Abstract : Aim: The aim of this study was to analyse whether gender inequality in the domestic sphere was associated with psychological distress among women and men. Methods: In a cohort study, all pupils in the last year of compulsory school in a middle-sized industrial town in northern Sweden were followed until the age of 42. For this study a sample of cohabiting participants (n=372 women, 352 men) was selected. Gender inequality was measured as perceptions of gender inequality in the couple relationship, time spent on household work, responsibility for domestic work and childcare, and was analysed in relation to psychological distress, after taking possible background variables as well as earlier health status into account. Results: In the multivariate analyses, perception of gender inequality in the couple relationship was associated with psychological distress for both women (OR 2.23, CI 1.20 to 4.18) and men (OR 3.51, CI 1.69 to 7.31). For women only, taking whole responsibility for domestic work was associated with the outcome (OR 2.17, CI 1.05 to 4.48). For men, taking less than half of the responsibility for domestic work was associated with psychological distress (OR 2.25, CI 1.24 to 3.91). Conclusions: Gender inequality in the domestic sphere seems to be an important determinant of psychological distress for both women and men.